15th IEEE International Requirements Engineering Conference (RE 2007) 2007
DOI: 10.1109/re.2007.51
|View full text |Cite
|
Sign up to set email alerts
|

Collaboration Patterns and the Impact of Distance on Awareness in Requirements-Centred Social Networks

Abstract: Becauseof intense collaborative needs, requirements engineering is a challenge in global software development. How do distributed teams manage the development of requirements in environments that require significant cross-site collaboration and coordination? In this paper, we report research that used social network analysis to explore collaboration and awareness among team members during requirements management in an industrial distributed software team. Using the lens of a requirements-centred social network… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 11 publications
1
62
0
Order By: Relevance
“…Damian et al [57] suggested that working on the same or interdependent requirements could be considered a means of stakeholders' social interaction. They presented the concept of requirements-centric social network (RCSN) by defining social networks among stakeholders working on the same or interdependent requirements [57].…”
Section: Stakeholders' Social Interactionmentioning
confidence: 99%
See 3 more Smart Citations
“…Damian et al [57] suggested that working on the same or interdependent requirements could be considered a means of stakeholders' social interaction. They presented the concept of requirements-centric social network (RCSN) by defining social networks among stakeholders working on the same or interdependent requirements [57].…”
Section: Stakeholders' Social Interactionmentioning
confidence: 99%
“…They presented the concept of requirements-centric social network (RCSN) by defining social networks among stakeholders working on the same or interdependent requirements [57]. In order to identify and prioritize stakeholders and their requirements, Lim and colleagues [107] asked the already identified stakeholders to recommend other stakeholders and built social network based on their recommendations.…”
Section: Stakeholders' Social Interactionmentioning
confidence: 99%
See 2 more Smart Citations
“…[34] note that "most of the bridges we have found in our research and in the literature are not ones that were developed intentionally as part of organization strategy, but units that have grown out of organizational need, or of the team positioning themselves in this role.". As an example in a study conducted among several distributed networks of people working on requirements engineering, results showed that on average, about one third of the team members were emergent roles [14]. In another study, it was observed that although teams were designed to communicate "freely", i.e.…”
Section: B Cooperationmentioning
confidence: 99%